Study of Cutaneous Manifestations in Patients with Polycystic Ovarian Syndrome Attending a Tertiary Care Centre - Khalid, Aleena Binte; Sibghatullah Rao,; Umaima Malik,; Maria Sargana,; Amna Akbar, (Indus Journal of Bioscience Research, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common reproductive, metabolic, and psychological condition affecting up to 18% of women. It often manifests with dermatological symptoms, which may provide early diagnostic clues. Understanding the frequency and characteristics of these cutaneous manifestations is essential for effective management. Objective: To determine the frequency of cutaneous manifestations associated with PCOS. Materials and Methods: This descriptive cross-sectional study was conducted in the Department of Dermatology, CMH Multan, from June to December 2024. A total of 219 adult non-pregnant females aged 18–40 years, fulfilling the Rotterdam-2003 diagnostic criteria for PCOS, were enrolled through non-probability consecutive sampling. Participants with other endocrine disorders or hormonal disturbances were excluded. Clinical and anthropometric data, including BMI and cutaneous manifestations (hirsutism, acne, androgenic alopecia, seborrhea, acanthosis nigricans, and skin tags), were recorded. Data were analyzed using SPSS v26, with a Chi-Square test applied for significance. Results: The mean age of participants was 24.15 ± 7.10 years, and the mean BMI was 25.84 ± 6.00 kg/m². Hirsutism (93.26%) was the most prevalent manifestation, followed by androgenic alopecia (91.80%), seborrhea (89.40%), and acne (85.60%). Acanthosis nigricans and skin tags were present in 56.30% and 33.20%, respectively. Obese participants exhibited significantly higher rates of hirsutism compared to non-obese participants (82.5% vs. 39.7%, p<0.0001). Conclusion: Cutaneous manifestations are frequent in PCOS, with obesity significantly exacerbating hirsutism. Early dermatological assessment can aid in timely diagnosis and management of PCOS.